Analysis of Leadership Style, Motivation and Discipline of Employee Performance at Pragaan Public Health Center Sumenep District - Khairul Anwar, Raden Bagus; Indasah, Indasah (Journal for Quality in Public Health, 2021)
The role of health workers in administering health services is very important, especially as health service implementers, so it is natural that the ability and performance of health workers are one of the determinants of success in health services.. The purpose of this study was to analyze the influence of leadership style, motivation and discipline on employee performance at the public health center Pragaan, Sumenep Regency. The design of this study was an observational quantitative study with a cross sectional approach with the focus of the research being directed at analyzing the influence of leadership style, motivation and discipline on employee performance at public health center Pragaan, Sumenep Regency.with a population of 175 respondents and a sample of 114 respondents who were drawn using the simple random sampling technique. The findings showed that almost half of the respondents had a leadership style in the moderate category as many as 56 respondents (49.1%). Almost half of the respondents have medium category motivation as many as 48 respondents (42.1%). Nearly half of the respondents have sufficient work discipline as many as 49 respondents (43%). Nearly half of the respondents have a moderate performance category as many as 51 respondents (44.7%). Based on the results of the Multiple Linear Regression analysis, it shows that with a p-value of 0.000 <0.05, H0 is rejected and H1 is accepted, so it is concluded that simultaneously there is an influence of leadership style, Motivation and work discipline on employee performance at the Pragaan Public Health Center, Sumenep Regency with a magnitude of the influence of 75%. As a leader, the head of the puskesmas can provide appropriate direction, input and supervision to his subordinates so that the performance carried out by health workers can be well organized.